Guidelines for Promoting Political Literacy among High School Students - Jhetson, Prasai; Sawekngam, Wichai (An Online Journal of Education, 2024)
This research aimed to 1) study the key components and specific behavioral indicators of political literacy among high school students and 2) propose guidelines for promoting political literacy among high school students. The study employed a qualitative research method, including document synthesis, interviews, focus group discussions, and content analysis. The target participants were three groups of experts: political science, curriculum and teaching specialists, and social studies teachers. The research tools included interviews, indicator validation forms, focus group discussion records, and performance evaluation forms. Data were analyzed using content analysis. The research findings revealed that: 1) The key components of political literacy for high school students consisted of five main elements: political knowledge, political information literacy, self-awareness of political perspectives, tolerance for political differences, and political expression and participation. 2) The guidelines for promoting political literacy among high school students focused on (1) developing all five components holistically; (2) following the SECMAR principles; (3) utilizing the 6D Model; (4) emphasizing integrated learning into strategies and learning methods, experiential learning, and decision-making skill development; (5) dividing the promotion of political literacy into three level; (6) dividing the implementation models in schools into two types: integration into existing courses and promotion through extracurricular activities; and (7) integrating the key principles, including holistic evaluation, real-life practice-based assessment, and assessment of thinking and decision-making skills via scenario-based evaluations, into the assessment of political literacy.